The Effect of Foehn‐Induced Surface Melt on Firn Evolution Over the Northeast Antarctic Peninsula. Issue 7 (11th April 2019) - Datta, Rajashree Tri; Tedesco, Marco; Fettweis, Xavier; Agosta, Cecile; Lhermitte, Stef; Lenaerts, Jan T. M.; Wever, Nander
Abstract: Surface meltwater ponding has been implicated as a major driver for recent ice shelf collapse as well as the speedup of tributary glaciers in the northeast Antarctic Peninsula. Surface melt on the NAP is impacted by the strength and frequency of westerly winds, which result in sporadic foehn flow. We estimate changes in the frequency of foehn flow and the associated impact on snow melt, density, and the percolation depth of meltwater over the period 1982–2017 using a regional climate model and passive microwave data. The first of two methods extracts spatial patterns of melt occurrence using empirical orthogonal function analysis. The second method applies the Foehn Index, introduced here to capture foehn occurrence over the full study domain. Both methods show substantial foehn‐induced melt late in the melt season since 2015, resulting in compounded densification of the near‐surface snow, with potential implications for future ice shelf stability. Plain Language Summary: Surface melt and the ponding of water on the surface has been linked to recent ice shelf collapse in the northeast Antarctic Peninsula, which includes the Larsen C ice shelf, one of the regions in Antarctica that is most vulnerable to a changing climate. Melt can be caused either by high temperatures or by foehn winds, that is, a hot, dry wind on the downwind side of a mountain range. To determine when foehn winds occurred from 1982 to 2017, and how much surface melt they produced, we use two methods. The first method finds recurring patterns of melt on the northeast Antarctic Peninsula from both satellite observations and models and determines which patterns are produced by foehn conditions. The second method uses simulated atmospheric conditions to determine when and over how much surface area foehn conditions occur and then calculates the melt produced at the same time. Both methods find high levels of foehn‐induced melt after the summer melt season occurring since 2015, resulting in high‐density snow near the surface in regions where foehn winds are common. If similar conditions persist into the future, late‐season and autumn melt could have substantial ramifications for the health of the Larsen C ice shelf. Key Points: A long‐term record of foehn‐induced melt is calculated from a regional climate model via two methods We introduce the Foehn Index which captures foehn intensity over space and time Late‐season foehn‐induced melt between 2015 and 2017 produced compounded densification in the upper snowpack resulting in increasing runoff